(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Much of the available literature that has examined the diffusion of mobile banking has tended to focus on the developed societies where these innovations had initially been introduced. As such, there is a paucity of studies on the diffusion of innovations that have focused on mobile banking in developing contexts generally and in particular in South Africa. This study focused on convenience, cost/price, trust and the original variables of the extended technology acceptance model by Venkatesh and Davis (2000). The study has further explored the main influencers for mobile banking among customers on the basis of their perceptions of important attributes of the electronic banking technology.